The THE IMPLEMENTATION OF ENGLISH LANGUAGE SKILLS TEACHING AND LEARNING DURING THE PANDEMIC OF COVID-19 - Tri Pujiani; Putra Akbar Wibawa; Nur Azzizatun Zahro; Intan Fadilah Iryaninda (J-LEE - Journal of Law, English, and Economics, 2021)
Since March 2020, based on Circular letter dated 4 March 2020, Indonesia has implemented online learning to stop the outbreak of covid-19 virus. This immediate shift requires many adjustments, especially in skill subjects such as English Language Skills. This research aimed to describe the implementation of English Language Skills teaching during covid-19 pandemic in some universities in Indonesia. This research was a descriptive qualitative research with questionnaire used to obtain the data. The respondents of this research were English lecturers from some universities in Indonesia as many as 25 lecturers. The result showed that the biggest problem in online learning was internet connection. The lecturers were required to enhance their technology literacy and to be creative in designing the learning process to motivate the students to learn. Besides, the students needed to be more active in searching learning sources independently. The active participations of both lecturers and students are definitely important for the effectiveness of online teaching and learning. It is expected that this research may be reference for all education practitioners in implementing online learning for English Language Skills subjects